Antibacterial Activities of the Extracts of Sponge-Associated Fungus Trichoderma longibrachiatum against Pathogenic Bacteria - Sedjati, Sri; Ambariyanto, Ambariyanto; Trianto, Agus; Supriyantini, Endang; Ridlo, Ali; Bahry, Muhammad Syaifudien; Wismayanti, Gita; Radjasa, ocky Karna; McCauley, Erin (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2020)
This study aims to explore the antibacterial potential of a sponge-associated fungus Trichoderma longibrachiatum isolated from Ternate waters, North Maluku, Eastern Indonesia. Various culture media were used to stimulate the production of secondary metabolites in T. longibrachiatum. The isolate was cultured in various media for 6-9 days. Then, the antibacterial activities of the ethyl acetate extracts were assayed against pathogenic bacteria of Multi-Drug Resistant (MDR) strain (Pseudomonas aeruginosa, Staphylococcus aureus, Klebsiella pneumoniae, and Bacillus cereus). The results showed that all extracts had similar profiles on the thin layer chromatography. However, two of the most potent extracts were produced from the PCA and MEA media for 9 days. These extracts inhibited methicillin-resistant S. aureus (MRSA) (12.48 mm and 12.27 mm); B. cereus (12.11 mm and 12.12 mm); K. pneumoniae (12.40 mm and 10.76 mm); and P. aeruginosa (11.59 mm and 8.69 mm) at concentrations 500 mg/disc. In conclusion, the fungus T. longibrachiatum that was cultured in PCA and MEA media had the potential to produce antibacterial compounds against MDR pathogens and both had similar compounds.Â  Meanwhile, theÂ  ethyl acetate extracts from fungus cultured in the TPA and TA media were inactive against all tested bacteria